Broadening Our Scope: International Collaboration for Retooling the Academic Library. Issue 4 (18th May 2016) - Smith, Bonnie J.
Abstract : The internationalization of higher education and the continuing expansion of technology as a means for learning and sharing information have radically changed the way in which academic libraries offer services and perform outreach. Retooling is essential to maintaining a vibrant and responsive workforce. Continual innovation on the part of training and development professionals is required to manage the expansion of relevant competencies. Through analysis of the current literature and using the results of an exploratory study, which engaged library associations globally, the author demonstrates the need and desire for increased international dialog and collaboration in the area of professional development.